Elderly in the UAE: Policy-oriented Study - Albahri, Ghanima; Alothman, Hussein (Al-Adab Journal, 2025)
This research aims to identify the main pillars of social policy for the elderly in the UAE, as well as to examine the existence and availability of necessary laws and services to protect the rights of the elderly and ensure the fulfillment of their needs. The study employed a descriptive method, with researchers accessing available data related to elderly policy in the UAE to conduct an intensive review of national legislation, laws, services, and programs related to the policy. The results revealed that the policy is based on seven pillars: healthcare, community involvement, effective civic participation, housing and infrastructure, financial stability, safety and security, and quality of future life. It was also found that the UAE government is highly committed to ensuring the rights of the elderly by issuing several legislations and laws, especially Federal Law No. 9 of 2019 on the Rights of Senior Emiratis, which was tailored for senior citizens in the UAE. Additionally, the results showed that the government has allocated significant resources to support the provision of comprehensive services for the elderly in various sectors, particularly health, protection, integration, rehabilitation, education, mobility, and financial support services. However, the research indicated that improvements are needed in the field of elderly empowerment, access to the digital world, technology integration, and effective participation from all stakeholders. Several corrective measures were proposed by the researchers to improve the policy in the country, the most prominent of which is the establishment of a national database for the elderly and conducting further quantitative and qualitative research, in addition to ensuring the elimination of technological illiteracy and promoting the active participation of the elderly in policy-making and all aspects of life.